METAL BEAMS, REINFORCED BONGS - Kh. M. Muselemov; O. M. Ustarkhanov; A. K. Yusupov (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
Focuses on the design and calculation scheme trussed girders with one and with two enclosures. Provides cross-section elements, their selection and definition of effort. On the basis of alternative engineering is a comparative analysis, are given in table steel consumption for different variants trussed girders, by which to judge the rationality of the design.